Some Functional, Chemical, and Sensory Characteristics of Cactus Pear Rice-Based Extrudates - El-Samahy, S. K.; Abd El-Hady, E. A.; Habiba, R. A.; Moussa-Ayoub, T. E. (Journal of the Professional Association for Cactus Development, 2007)
Both orange-yellow and red cactus pear pulps were concentrated (to 40ºBrix), and then added to rice grits to produce a delectable product of rice-based extrudates. Both concentrated pulps were added to rice grits in five levels 0, 5, 10, 15 and 20%. The effects of added concentrated pulps on some physical (expansion ratio (ER), bulk density (BD), water absorption index (WAI), water solubility index (WSI), breaking strength (BS), and color attributes (L*, a* and b*); chemical (moisture, total carbohydrate, crude protein, crude fat and ash); and sensory (taste, crispness, chewiness, odor, color, pore distribution, surface characteristics, and overall acceptability) characteristics of extruded products were evaluated. The expansion ratio (ER), water absorption index (WAI), and water soluble index (WSI) of all products decreased by increasing the added concentrated-pulp ratio, while breaking strength (BS) decreased up to 10% of the added ratio, then increased. Bulk density, ash content and color attributes (a* and b*) increased for all extruded products. Adding both concentrated cactus pear pulps to rice flour extremely enhanced the sensory characteristics of final extruded products, and the obtained results showed the possibility of producing a new value-added snack-type extrudate based on cactus pear pulp concentrates.